The experience of bearing a child: implications on body boundaries and their link to preterm birth - Nina Spaegele; Julia Ditzer; Mariana Rodrigues; Anat Talmon (BMC, 2024)
Abstract Background Preterm birth, which occurs when a baby is born before 37 weeks, has enormous implications for public health. It is the leading cause of infant death and mortality in children under the age of five. Unfortunately, the multifaceted causes of preterm birth are not fully understood. One construct that has received increasing attention in women's transition to motherhood is body boundaries, i.e., the metaphorical barriers that separate the self from the outer, surrounding "not self." This study aims to examine the role of well-defined and disturbed body boundaries in predicting preterm birth. Methods A sample of 655 Israeli pregnant women reported their sense of body boundaries (BBS, as measured by the Sense of Body Boundaries Survey) pre- and postnatally. We performed a General Linear Model (GLM) testing the effect of the BBS total score on the days women delivered before their due date and controlling for whether it was the women's first child. Results Our GLMs controlling for whether it was the women's first child showed that the BBS total mean exhibited a significant predictive effect on the number of days delivered before the due date (F(57,313) = 3.65, p < .001). Conclusions These results demonstrate heterogeneity in women's sense of body boundaries during pregnancy and are the first to disentangle a link between disturbed body boundaries and preterm birth. Mediating mechanisms in this relation, e.g., psychosocial stress, as well as clinical implications are discussed in detail.